VITAMIN D PADA ASMA BRONKIAL - Setyawan, Yuswanto (Universitas Ciputra Surabaya, 2024)
Bronchial asthma is a lung disease characterized by reversible airway obstruction both spontaneously and with treatment, characterized by airways inflammation and hyperreactivity to various stimuli. Until now, the most effective treatment for asthma are corticosteroids and β-agonists, while the administration of prophylactic drugs is often less effective and often causes very disturbing side effects. Vitamin D is a group of fat-soluble secosteroids. Vitamin D has functions in modulating neuromuscular function, reducing inflammation and influencing the work of various genes that regulate cell proliferation, differentiation and apoptosis. Research shows that low levels of vitamin D are associated with increased allergy markers and asthma levels. Vitamin D is believed to play a role in asthma by inhibiting respiratory tract smooth muscle proliferation via hyperphosphorylation of the retinoblastoma protein and activation of checkpoint kinase 1 (Chk1). Vitamin D has recently been considered as a treatment for asthma.